Evaluation and the Persistence of Innovation The Louisiana Special Plan Upgrading Reading (SPUR) Project - Hoffman, Lee McGraw ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This paper examines the effect of a formal evaluation process upon educational change--specifically, the adoption of innovative reading programs and practices--at different organizational levels of implementation. Because of the size of the project (62 school systems, 142 designated schools, three sets of categorical funded projects), the evaluation design is very simple. SPUR's organization as perceived by participants, self-reports of teacher reading instruction practices, and general professional development and teacher inservice activities were measured through survey instruments. The evaluation describes SPUR in terms of the above data and correlates student reading gains with these data plus other indicators of the degree to which the school has followed SPUR-recommended standards and practices. The evaluation had three positive uses in the SPUR program to date: bookkeeping, self-definition, and program change. Acceptance of the evaluation process and use of it or its measures appears to depend upon the extent to which the person or group has participated in developing and conducting the evaluation. Outcomes suggest there are benefits to be gained from involving clients in evaluation activities to the fullest extent. (Author/GK)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (65th, Los Angeles, CA, April 13-17, 1981).
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Change; Elementary Education; Evaluation Methods; Program Evaluation; Reading Programs; Research Utilization; State Programs; Louisiana Special Plan Upgrading Reading Project; Evaluation Utilization -- Louisiana; Speeches/Meeting Papers; Reports, Descriptive